Os 45 anos da cerâmica Santa Edwiges - Sales, Juscelino Chaves (2012)
The Ceramics Ltda. St. Hedwig came into operation in 1967 in the area located in Maracanaú which belonged to the town of Maraguape in Ceará. Today is the state’s oldest pottery in operation is worth high lighting that it is rented to another person who does not belong to the family of the founder. Throughout Its existence it only manufactured products such as red ceramic tiles combogós, PM6, sealing, ceramic blocks brick and solid blocks. This paper showed why this ceramic keeps ruing after so many years, as well as the difficulties encountered at the time such as obtaining raw materials fuel for sintering the bricks, urbanization in the vicinity of manufactures among other difficulties. Also this paper shows the advantages that make the plant still in operation. Currently the only manufactures ceramic blocks for the construction fence.